Analisis Nilai-Nilai Kearifan Lokal dari Segi Unsur Budaya dalam Novel Tenggelamnya Kapal Van Der Wijck (Kajian: Antropologi Sastra): Analysis of Local Wisdom Values in terms of Cultural Elements in the Novel “Tenggelamnya Kapal Van der Wijck” (Study: Literary Anthropology) - Nofita, Ririn; Puspitasari, Ayu; Yuvindra, Bastian Yusuf; Krismonita, Fanie Yuniar (Kibas Cenderawasih, 2024)
This study aims to describe the value of local wisdom in terms of cultural elements in the novel Tenggelamnya Kapal Van der Wijck. Qualitative descriptive method. Data collection techniques observing and note. Data analysis technique Miles & Hunberman. The results of research: (1)Language: Minangkabau, (2)Knowledge system: the mindset that descent and wealth are everything, as well as the development of health sciences, (3)Social organizations: ninik-mamak deliberations and the Sumatran Children's Club. (4)Equipment and technology systems: luxury ships and modernization in urban areas, (5)Live production systems: exports of forest products, fishing, and authors, (6)Religious systems: Islam, and (7)Arts: saga performances.